Keberlangsungan Inovasi Gerakan Masyarakat Peduli Ibu dan Balita (GEMPITA) pada Ibu Hamil Resiko Tinggi - Marchamah, Dwi Nur Siti; Arumsari, Wahyuni (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: The need for innovation in the public sector, one of which is health, is important. The Covid-19 pandemic has caused an increase in the number of illnesses experienced by pregnant women.Objective: The research aims to find out the health program innovations that have been carried out in detail and in-depth at Puskesmas Karangtengah as the initiator of GEMPITA.Methods: The research uses a qualitative descriptive approach. Primary data includes input, process, and overall output components for GEMPITA. There were 4 informants, namely the Community Health Center Midwife Coordinator, Community Health Center Midwife, Community Health Center Nutrition Coordinator, and Head of Village Midwife. Data was analyzed using content analysis.Results: GEMPITA accommodates the implementation of integrated ANC. Sources of funding come from BOK, APBD, and village funds. Programs are periodically proposed through RAB on the BOK scheme in the form of PoA. Health program planning activities at community health centers based on PWS.Conclusion: Involvement in implementing GEMPITA includes community health center midwives, nutrition officers, laboratory officers, pharmacists, health promotion officers, general practitioners, dentists, village midwives, cadres, and village officials. Increasing the participation of all stakeholders and the community includes promotive efforts, preventive efforts, and community empowerment efforts.